2015
DOI: 10.3329/baj.v17i1.23676
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic differences in growth and ions accumulation in soybean under NaCL salinity and water stress conditions

Abstract: Salt and water stress tolerance of the seven soybean genotypes viz. BARI Soybean 6, BD 2329, BD 2342, AGS 95, BGH 02026, Galarsum and BD 2331 were evaluated for their performance at 0 and 100 mM NaCl under well watered & water stress (watering with 70% depletion of available water at wilting) conditions at the Banghabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur. The results indicated that all the growth parameters like plant height, shoot dry weight, root dry weight and dry matter di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
4
19
0
Order By: Relevance
“…On the contrary, the shoot dry weight of tolerant genotypes Shohag, BARI Soybean-6, BARI Soybean-5 and BD2331 were affected the least by the stress. A similar finding was observed by Khan et al (2014) in soybean, Eureka et al (2000) and OO et al (2008) in mungbean. Leaf area has been frequently reported to have a close relationship with crop growth (OO et al, 2008;Anyia and Herzog, 2004).…”
Section: Shoot and Root Dry Weightsupporting
confidence: 74%
See 2 more Smart Citations
“…On the contrary, the shoot dry weight of tolerant genotypes Shohag, BARI Soybean-6, BARI Soybean-5 and BD2331 were affected the least by the stress. A similar finding was observed by Khan et al (2014) in soybean, Eureka et al (2000) and OO et al (2008) in mungbean. Leaf area has been frequently reported to have a close relationship with crop growth (OO et al, 2008;Anyia and Herzog, 2004).…”
Section: Shoot and Root Dry Weightsupporting
confidence: 74%
“…The differences in plant height reduction among the genotypes mainly due to genotypic differences. Water stress induced reduction in plant height was also observed by Khan et al (2014) in soybean. The decrease in plant height could be resulted from a reduction in plant photosynthetic efficiency as reported by Hamid et al (1990).…”
Section: Plant Heightmentioning
confidence: 70%
See 1 more Smart Citation
“…The reduction in relative shoot and root dry weight might be due to water shortage and sodium ionic damage. Khan et al (2014) also reported that relative shoot and root dry weight decreased significantly in soybean genotype under salt and water stress condition due to water shortage and sodium ionic damage.…”
Section: Resultsmentioning
confidence: 99%
“…Root dry weight slightly decreased under salt and water stress at all the growth stages. The reduction in root dry weight of soybean due to salt and water stress was also reported by Khan et al (2014 Relative shoot and root dry weight…”
Section: Resultsmentioning
confidence: 99%